Effect of foliar application and fertigation on micronutrient absorption efficiency and productivity of sweet pepper in calcareous soil in Iraq - Ziyad A. Humod Al-Ogaidi; Bushra Mahmoud Alwan (Kufa Journal for Agricultural Sciences)
A field experiment was carried out in a private greenhouse farm located in Al-Madaen city / old Diyala Bridge / Western Tuwaitha village (N 44, 29,47-E 36, 33,11) in the agricultural season 2020/2021 to study the effect of micronutrient absorption efficiency and yield of sweet pepper was grown in calcareous soil, Dutch Olombus sweet pepper was planted and used the nutrients (manganese at a concentration of 30 mg.l-1, copper at ca concentration of 25 mg.l-1. Iron at a concentration of 50 mg.l-1, zinc at a concentration of 60 mg.l-1, The factorial experiment was carried out according to the split-plot design with two methods of nutrients application, one by spraying  on shoots foliar application and the other with irrigation water, 16 treatments were used for each method of addition, which consisted of single, double, triple and quadruple addition of the nutrients that used in the experiment, with the control treatment for each method of addition and with three replicates for each treatment, there were 30 additions duration of the experiment,  the first edition took place after two weeks of cultivation in the field, the period between each addition was one week, and the macronutrients N, P, K were used in concentrations (425 Kg N ha-1,175kg P ha-1 and 250 kg K ha-1 ), the results of highest cumulative yield was for the Fe+ Zn+ Mn treatment which added by spraying on shoots, which amounted to 159.15 Mg h-1., It also showed a highly significant superiority for all treatments of adding micronutrients sprayed on the shoot over the corresponding treatments of adding these nutrients with irrigation water on the efficiency of absorption of micronutrients in the fruits of the sweet pepper plant. The Fe+ Mn treatment gave the highest value for the iron absorption efficiency of 341.3%, while the Zn+ Mn+ Cu treatment gave the highest value for the zinc absorption efficiency of 113.17%. As for the manganese absorption efficiency, the Fe+ Mn treatment gave the highest value of 517.2%. As for the absorption efficiency of copper, the Fe+ Mn+ Cu treatment gave the highest value of 217.2%.